Leadership in Action : a Question of Leadership - The Terrorist Attacks on September 11 Brought Stark Reminders that Extraordinary Circumstances Require Extraordinary Leadership. What Can Leaders do to be as Effective as Possible During a Crisis? - Klann, Gene (Center for Creative Leadership, 2001)
Leaders need to be in the thick of things, and their followers need to know it. In the midst of a crisis, emotionally intelligent leaders provide structure and stability.